Electrochemically Reduced Water Protects Neural Cells from Oxidative Damage. (14th October 2014) - Kashiwagi, Taichi; Yan, Hanxu; Hamasaki, Takeki; Kinjo, Tomoya; Nakamichi, Noboru; Teruya, Kiichiro; Kabayama, Shigeru; Shirahata, Sanetaka
Abstract : Aging-related neurodegenerative disorders are closely associated with mitochondrial dysfunction and oxidative stresses and their incidence tends to increase with aging. Brain is the most vulnerable to reactive species generated by a higher rate of oxygen consumption and glucose utilization compared to other organs. Electrochemically reduced water (ERW) was demonstrated to scavenge reactive oxygen species (ROS) in several cell types. In the present study, the protective effect of ERW against hydrogen peroxide (H2 O2 ) and nitric oxide (NO) was investigated in several rodent neuronal cell lines and primary cells. ERW was found to significantly suppress H2 O2 (50–200  μ M) induced PC12 and SFME cell deaths. ERW scavenged intracellular ROS and exhibited a protective effect against neuronal network damage caused by 200  μ M H2 O2 in N1E-115 cells. ERW significantly suppressed NO-induced cytotoxicity in PC12 cells despite the fact that it did not have the ability to scavenge intracellular NO. ERW significantly suppressed both glutamate induced Ca 2+ influx and the resulting cytotoxicity in primary cells. These results collectively demonstrated for the first time that ERW protects several types of neuronal cells by scavenging ROS because of the presence of hydrogen and platinum nanoparticles dissolved in ERW.